Tailoring C60 for Efficient Inorganic CsPbI2Br Perovskite Solar Cells and Modules. Issue 8 (15th January 2020) - Liu, Chong; Yang, Yuzhao; Zhang, Cuiling; Wu, Shaohang; Wei, Liyu; Guo, Fei; Arumugam, Gowri Manohari; Hu, Jinlong; Liu, Xingyuan; Lin, Jie; Schropp, Ruud E. I.; Mai, Yaohua
Abstract: Although inorganic perovskite solar cells (PSCs) are promising in thermal stability, their large open‐circuit voltage ( V OC ) deficit and difficulty in large‐area preparation still limit their development toward commercialization. The present work tailors C60 via a codoping strategy to construct an efficient electron‐transporting layer (ETL), leading to a significant improvement in V OC of the inverted inorganic CsPbI2 Br PSC. Specifically, tris(pentafluorophenyl)borane (TPFPB) is introduced as a dopant to lower the lowest unoccupied molecular orbital (LUMO) level of the C60 layer by forming a Lewis acidic adduct. The enlarged free energy difference provides a favorable enhancement in electron injection and thereby reduces charge recombination. Subsequently, a nonhygroscopic lithium salt (LiClO4 ) is added to increase electron mobility and conductivity of the film, leading to a reduction in the device hysteresis and facilitating the fabrication of a large‐area device. Finally, the as‐optimized inorganic CsPbI2 Br PSCs gain a champion power conversion efficiency (PCE) of 15.19%, with a stabilized power output (SPO) of 14.21% (0.09 cm 2 ). More importantly, this work also demonstrates a record PCE of 14.44% for large‐area inorganic CsPbI2 Br PSCs (1.0 cm 2 ) and reports the first inorganic perovskite solar module with the excellent efficiency exceeding 12% (10.92 cm 2 ) by a self‐developed quasi‐curved heating method. Abstract : A Lewis acid tris(pentafluorophenyl)borane and nonhygroscopic lithium salt (LiClO4 ) codoping strategy is introduced to tailor C60 and fabricate highly efficient inorganic CsPbI2 Br perovskite solar cells with reduced hysteresis. Consequently, square‐centimeter inorganic CsPbI2 Br perovskite solar cells yield a record power conversion efficiency (PCE) of 14.44%. In addition, the first inorganic perovskite solar module with an efficiency exceeding 12% is reported, using a self‐developed quasi‐curved heating method.